Immobilization of two (R)‐Amine Transaminases on an Optimized Chitosan Support for the Enzymatic Synthesis of Optically Pure Amines. Issue 2 (9th October 2012) - Mallin, Hendrik; Menyes, Ulf; Vorhaben, Torge; Höhne, Matthias; Bornscheuer, Uwe T.
Abstract Two (R)‐selective amine transaminases from Gibberella zeae (GibZea) and from Neosartorya fischeri (NeoFis) were immobilized on chitosan as a carrier to improve their application in the biocatalytic synthesis of chiral (R)‐amines. An (S)‐selective enzyme from Vibrio fluvialis (VfTA) was used for comparison. After improving the immobilization conditions, all enzymes could be efficiently immobilized. Additionally, the thermal stability of GibZea and NeoFis could be improved and also a slight shift of the pH optimum was observed for GibZea. All enzymes showed good activity in the conversion of α‐methylbenzylamine. In the asymmetric synthesis of (R)‐2‐aminohexane from the corresponding ketone, a 13.4‐fold higher conversion (>99 %) was found for the immobilized GibZea compared to the free enzyme. Hence, the covalent binding with glutaraldehyde of these enzymes on chitosan beads resulted in a significant stabilization of the amine transaminases investigated.